Exploring the tourism potentials of cistercian monastery, awhum, Southeastern Nigeria (2013)
This paper is a product of a study on the tourism potentials of Awhum Monastery in Enugu State, south-eastern Nigeria. The paper presents a 'thick description ' (cf. Geertz, 1973) and interpretation of occurrences within the space and, employing life history technique, explores the meanings and significances which the site holds for the tourists. Other tourist attractions around (he centre and the nature of the pilgrims' interactions with these sites are also identified. The study discovers that Cistercian Monastery holds a great promise for religious tourism development. Both local and foreign tourists visit the monastery for the purpose of an encounter with the supernatural, an experience of inner transformation, thanksgiving and quest for solution to individual problems. Invariably, the Awhum Monastery-provides the context for Spirituality and Nature to intermingle: establishing divine encounter for the ultimate goal of spiritual reinvigoration for the religious tourists and refreshment for the eco-tourists.